Aromatase inhibitors in the treatment of breast cancer in post-menopausal female patients: an update - Schneider RE (Dove Medical Press, 2011)
Reva Schneider1, Ayman Barakat1, John Pippen1,2,3, Cynthia Osborne1,2,3 1Medical Oncology, Baylor-Sammons Cancer Center, 2Texas Oncology PA, 3US Oncology, Dallas, TX, USA Abstract: Estrogen and its metabolites play a significant role in the proliferation of hormone receptor-positive breast cancer. In postmenopausal women, aromatase inhibitors can significantly reduce estrogen levels by blocking enzyme-mediated estrogen synthesis within tissues. Third-generation aromatase inhibitors have now surpassed tamoxifen as first-line therapy for postmenopausal women with metastatic, hormone receptor-positive, breast cancer, showing improved response rates and time to progression. Aromatase inhibitors have shown incremental improvements in disease-free survival, lower local recurrence rates, lower metastatic recurrence rates, and a lower incidence of contralateral breast cancer over tamoxifen when used in the adjuvant setting. Aromatase inhibitors are recommended to be used as adjuvant therapy within the first 5 years of hormonal therapy and may be used either upfront for 5 years or sequenced with tamoxifen. No superiority of one aromatase inhibitor over another has yet been shown. The side effect profiles of aromatase inhibitors have some key differences compared with tamoxifen. These differences may influence treatment choices as well as impact compliance. Keywords: aromatase inhibitor, breast cancer, postmenopausal, hormonal therapy